Efficacies of remote ischemic preconditioning with different pressure modes on acclimatization in male trainees at a simulated altitude of 4 500 m - ZHANG Xucheng; ZHANG Xucheng; REN Yukun; REN Yukun; WANG Zhuo (陆军军医大学学报)
Objective‍　‍To compare the effects of upper limb remote ischemic preconditioning (RIPC) with different pressure modes on enhancing high-altitude acclimatization in healthy adult males rapidly exposed to high-altitude environments. Methods‍　‍In May 2024, 86 male adult residents living plain areas planning a high-altitude travel were recruited through advertisements in Chongqing by Department of Anesthesiology at the Second Affiliated Hospital of Army Medical University. The participants were randomly divided into a variable pressure training group (n=29), a constant pressure training group (n=29), and a control group (n=28). The variable pressure training group underwent RIPC training in a variable pressure mode [occlusion pressure was set at systolic blood pressure (SBP) + 40 mmHg], while the constant pressure training group received RIPC training in a constant pressure mode (fixed occlusion pressure of 200 mmHg). Both groups completed a bilateral upper limb RIPC training (twice daily, 5 cycles per time of 10-min occlusion followed by 5-min reperfusion) for 14 d. The control group received no such training. On the 3rd day post-training, all participants entered a simulated 4 500 m altitude chamber for 7 h. The incidence and severity of acute mountain sickness (AMS) were observed and evaluated, and the vital signs and cerebral tissue oxygenation index (CTOI) were recorded. Results‍　‍The incidence of AMS was 23.1% in the variable pressure training group (RR=0.4, 95%CI: 0.2~0.8, Chi-square=9.433, P=0.002) and 16.0% in the constant pressure training group (RR=0.2, 95%CI: 0.1~0.6, Chi-square=12.833, P<0.001), and both incidences were significantly lower than that in the control group (65.4%). The AMS symptom score in the variable pressure training group [1.5 (0.8, 3.0) vs (3.1±1.9), P=0.018] and the score in the constant pressure training group [1.0 (1.0, 2.0) vs (3.1±1.9), P=0.001] were significantly lower than that in the control group. The dizziness score was obviously lower in the variable pressure training group [0 (0, 1.0) vs 1.0 (1.0, 1.0), P=0.001] and the constant pressure training group [1.0 (0,1.0) vs 1.0 (1.0,1.0), P=0.003] than the control group, so was the fatigue/weakness score in the variable pressure training group [0 (0, 0.3) vs 1.0 (0,1.0), P=0.006], the constant pressure training group [0 vs 1.0(0,1.0), P<0.001], and the control group. The change of CTOI (ΔCTOI) in the variable pressure training group (P=0.010) and the constant pressure training group (P=0.042) was significantly lower than that in the control group. There were no statistical differences in the 3 groups in terms of SpO2, HR, SBP or DBP (P>0.05). What’s more, no significant differences were observed in the incidence of AMS, AMS score, dizziness score, fatigue/weakness score, or ΔCTOI between the variable pressure training group and the constant pressure training group (P>0.05). Conclusion‍　‍Both upper limb RIPC protocols, variable-pressure (SBP+40 mmHg) and fixed-pressure (200 mmHg), can effectively enhance high-altitude acclimatization by reducing AMS incidence, symptom severity, and cerebral oxygen desaturation.